The MITC4+ shell element in geometric nonlinear analysis. (June 2017) - Ko, Yeongbin; Lee, Phill-Seung; Bathe, Klaus-Jürgen
Highlights: We present the MITC4+ shell finite element for geometric nonlinear analysis. The Lagrangian formulation is employed allowing for large displacement kinematics. The element performance is demonstrated through the solutions of various problems. Abstract: We present the large displacement and rotation formulation of the new MITC4+ shell finite element recently proposed by Ko, Lee and Bathe for linear analysis (Ko et al., 2017) and demonstrate the performance in geometric nonlinear analysis. The element shows in linear analysis an almost ideal convergence behavior since shear and membrane locking is alleviated using the MITC approach. We show now that using the total Lagrangian formulation for large displacements and large rotations, the element is also robust and efficient in nonlinear analysis. We demonstrate the element performance through the solutions of various benchmark problems and reach the important conclusion that the MITC4+ shell element performs reliably and well even when the mesh undergoes large displacements and significant distortions during the response.